I Identifikasi Zat Pewarna Rhodamin B pada Liptint yang Beredar Via-Online Shop Menggunakan Kromatografi Lapis Tipis (KLT) dan Spektrofotometri Uv-Vis - Raihanah, Raihanah; fitriani, Siska Fitriani; Laili, Rofiatul Laili; Fatimah, Siti Fatimah; Sinta, Sinta Pratiwi; Siti Monica Anjani (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: Rhodamine B (Color K10) is a synthetic dye. This dye is a dye that is generally used in the textile industry as a clothing dye. Meanwhile, use is prohibited or not permitted by BPOM. However, the majority of people in Indonesia still do not know about the health risks of using Liptint in circulation, so the use of rhodamine B is still widespread due to being tempted by its cheap price. Objective: This study aims to determine the presence of Rhodamine B in Via-olshap liptint cosmetics which are in demand by most female consumers. Method:   The research method uses laboratory experimental research using descriptive analysis. So the data used is qualitative data (KLT) and quantitative data (UV-Vis spectrophotometry) Results:  He results of testing using KLT showed that the O brand liptint sample showed an Rf value of 0.08, indicating a discrepancy with the theory of a good Rf value. Meanwhile, the results of determining Rhodamine B levels in Liptint brand O were 28,644 mg/L Conclusion: The O brand liptint sold Via-Online Shop contains rhodamine B dye